Field Oriented Control of DFIG Based Wind Energy System Using Battery Energy Storage System. (2016) - Charles, C.M. Rahul; Vinod, V.; Jacob, Anju
Abstract: Wind power is the fastest growing source of electrical energy in the world today due to the increasing awareness of the environmental problems together with the rapid increase in the fuel cost and the power demand. Wind energy conversion using Doubly Fed Induction Generator (DFIG) is one of the most important types of renewable energy generations. The wind farm power output has large fluctuations due to sudden wind speed changes. Fluctuate power can often cause the violation of voltage and frequency limits in the weak system. It can be severe problem for the system stability also. The control system in the proposed arrangement of DFIG is able to reduce power fluctuation with the help of Battery Energy Storage System (BESS). In order to decouple the active and reactive powers generated by the machine, field oriented control is applied. As a result, high performance control of power can be achieved. The developed method has been tested through modelling a DFIG based wind energy system with BESS using SimPower System tools of MATLAB and simulated for operation as a grid connected system. The performance of DFIG based wind energy system demonstrates satisfactory performance under different wind speed conditions.